2012
DOI: 10.4161/derm.19201
|View full text |Cite
|
Sign up to set email alerts
|

Age and skin site related differences in steroid metabolism in male skin point to a key role of sebocytes in cutaneous hormone metabolism

Abstract: Hormone concentrations decline with aging. Up to now it was not clear, whether the decrease of hormone concentrations in blood samples are also present in cutaneous suction blister fluids, and whether skin from different anatomical sites shows different hormone concentrations.Analysis of suction blister fluids and paired blood samples from young (mean 27.8 y) and old (mean 62.6 y) male subjects by UPLC-MS/MS showed that DHEA concentration in blood samples was age-dependently significantly reduced, but increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 38 publications
(50 reference statements)
0
4
0
Order By: Relevance
“…Sebocytes can synthesize de novo cholesterol from acetate [36,37] and possess enzymatic machinery to produce sex steroids as well as glucocorticoids [38]. Confluent immortalized sebocytes [39] but not fibroblasts or keratinocytes express the enzyme 3β-HSD 1, which is responsible for the catalyzation of androstenedione from DHEA, as the first step for in situ testosterone formation. Hydrolysis of the circulating DHEA-S to DHEA through steroid sulfatase, takes mainly place in the sebaceous gland and the terminal hair follicle.…”
Section: Hs and The Pilosebaceous Unitmentioning
confidence: 99%
“…Sebocytes can synthesize de novo cholesterol from acetate [36,37] and possess enzymatic machinery to produce sex steroids as well as glucocorticoids [38]. Confluent immortalized sebocytes [39] but not fibroblasts or keratinocytes express the enzyme 3β-HSD 1, which is responsible for the catalyzation of androstenedione from DHEA, as the first step for in situ testosterone formation. Hydrolysis of the circulating DHEA-S to DHEA through steroid sulfatase, takes mainly place in the sebaceous gland and the terminal hair follicle.…”
Section: Hs and The Pilosebaceous Unitmentioning
confidence: 99%
“…The normal skin development and function is influenced by hormones: for example, the growth hormone stimulates keratinocyte proliferation [ 39 ], and thyroid hormones act directly on hair follicles [ 40 ]. The skin is a neuroendocrine organ, capable of hormone synthesis and release [ 41 ]: corticosteroids and sex hormones are synthesized and transformed [ 42 ] (with sebocytes playing a central role in cutaneous androgen metabolism [ 43 ]); catecholamines are synthesized by keratinocytes and melanocytes [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the following paper, Marina Rodriguez-Martin et al 10 discuss the question When are laboratory tests indicated in patients with vitiligo? In the next laboratory contribution, Markus Haag et al 11 investigate age and skin site related differences in steroid metabolism in male skin that point to a key role of sebocytes in cutaneous hormone metabolism. In the following clinical paper, Gerhard Lutz 12 reports on the association of Hair loss and hyperprolactinemia in women.…”
mentioning
confidence: 99%